Talent retention in a changing workplace: An investigation of variables considered important to South African talent - M. Birt; T. Wallis; G. Winternitz (South African Journal of Business Management, 2004)
In a workplace characterised by market-driven turnover, organisations attempting to retain those employees considered core to their purpose and continued success (referred to as `talent') face a huge challenge in determining the factors instrumental in minimising turnover amongst this group. This research aimed to identify the variables important to this group of valued employees, with a specific focus on the South African context. In addition, it was aimed to discover the relative importance of intrinsic and extrinsic variables to South African talent, particularly when these are considered as factors in their decisions to leave the organisation. It was found that South African talent placed great importance on intrinsic variables, although market opportunities were also considered highly significant in employees' decisions to leave. The variable of `Concern with employment equity and affirmative action' was revealed as a specifically South African variable, but it was not ranked as one of the participants' top five most important variables influencing retention.
Keywords: 650